Dynamic response regulation of non‐linear feedback linearised wind turbine using a two‐mass model. Issue 6 (3rd February 2017) - Lin, Zhongwei; Liu, Jizhen; Niu, Yuguang
Abstract : This study discusses the dynamic response regulation problem for the non‐linear wind turbine generator system (WTGS) based on the regional pole placement and geometric control techniques. First, the non‐linear model of WTGS is feedback linearised into a linear‐form system by the geometric control theory. Through constructing the appropriate diffeomorphism, the key variables of the original system have been remained in the transformed linear system, which sustains that the dynamic response could be adjusted in the transformed linear framework. Due to the multi‐input multi‐output and high‐order characteristics, the regional pole placement technique is applied on the feedback linearised WTGS, which can guarantee the limitation of several performances related to the dynamic response. In such a way, the dynamic response of WTGS can be regulated through the feedback linearisation and regional pole placement techniques. Simulation results for a 2 MW wind turbine show the effectiveness of the proposed method.